Internal capital markets and lending by multinational bank subsidiaries - de Haas, Ralph; van Lelyveld, Iman (Journal of Financial Intermediation, 2010)
We use new panel data on the intra-group ownership structure and the balance sheets of 45 of the largest multinational bank holdings to analyze what determines the credit growth of their subsidiaries. We find evidence for the existence of internal capital markets through which multinational banks manage the credit growth of their subsidiaries. Multinational bank subsidiaries with financially strong parent banks are able to expand their lending faster. As a result of parental support, foreign bank subsidiaries also do not need to rein in their credit supply during a financial crisis, while domestic banks need to do so.